2014
DOI: 10.1098/rspa.2013.0537
|View full text |Cite
|
Sign up to set email alerts
|

Transversally periodic solitary gravity–capillary waves

Abstract: When both gravity and surface tension effects are present, surface solitary water waves are known to exist in both two-and three-dimensional infinitely deep fluids. We describe here solutions bridging these two cases: travelling waves which are localized in the propagation direction and periodic in the transverse direction. These transversally periodic gravity-capillary solitary waves are found to be of either elevation or depression type, tend to plane waves below a critical transverse period and tend to soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The efficiency and accuracy of these numerical models for nonelectric surface water waves (i.e., E p = 0) were discussed by Wang and Milewski 17 and Nicholls and Reitich. 20…”
Section: Dirichlet-neumann Operatorsmentioning
confidence: 99%
“…The efficiency and accuracy of these numerical models for nonelectric surface water waves (i.e., E p = 0) were discussed by Wang and Milewski 17 and Nicholls and Reitich. 20…”
Section: Dirichlet-neumann Operatorsmentioning
confidence: 99%
“…28 One of these waves, namely, the long wave, is traditionally named a gravitational wave, whereas the other one, or the short one with a positive dispersion, is called a capillary wave. In one of the recent papers, 29 the authors obtained the profiles of doublefrequency waves based on a numerical solution of non-linear equations describing capillary-gravitational waves.…”
Section: The Origin and The Physical Nature Of Quantum Oscillationsmentioning
confidence: 99%
“…Surface elevation of the envelope of gravity-capillary solitary waves perturbed by their most unstable modes corresponding to Ω = 0, q = 1.01 and Ω = 0.10, q = 1.08 are shown in figure 9. These waves which are localized in the direction of propagation and periodic in the transverse direction have been investigated by Milewski & Wang (2014). This new solution found by the latter authors was called transversally periodic plane solitary wave.…”
Section: Transverse Instability Of the Envelope Of Gravity-capillary mentioning
confidence: 99%
“…Our purpose is not to consider three-dimensional localized solitary gravity-capillary waves. Akers & Milewski (2009), Akers & Milewski (2010), Wang & Milewski (2012) and Milewski & Wang (2014) used several model equations to investigate numerically the stability of two-dimensional and three-dimensional gravity-capillary solitary waves in deep water. Regarding two-dimensional waves they found that both gravity-capillary solitary waves of elevation and depression are unstable to transverse perturbations.…”
Section: Introductionmentioning
confidence: 99%